Spatial Network Resource Scheduling Based on Joint MPTCP with SDN for SDN/NFV Architecture - Min JIA; Jia GUO; Meilin XU; Qing GUO; Xuemai GU (天地一体化信息网络)
The space network is mainly composed of satellite networks of various architectures with many network nodes.Compared with the ground network,the nodes in the satellite network are diff cult to observe and control,and the network equipment is extremely expensive.The rapid increase in the number of users has brought a great burden to the network,and at the same time caused the network resources to be unreasonably used.The application of traditional network architecture to large-scale satellite networks results in the inability to fl exibly confi gure the network and uneven resource allocation.Aim to the above problems,a space network resource scheduling system based on SDN(software defi ned network)/NFV(network function virtualization) architecture was proposed to realized real-time monitoring of space network resources.At the same time,it combined MPTCP (multipath TCP) and SDN to completed the fl exible confi guration of the space network and the rational use of its resources.It improved the throughput of the network.